1998
DOI: 10.1002/(sici)1099-0690(199810)1998:10<2209::aid-ejoc2209>3.3.co;2-7
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Substituents on the Degenerate Cope Rearrangement of Semibullvalenes and Barbaralanes

Abstract: The activation parameters [∆G (200 K), ∆H , and ∆S ] for compounds, together with those for related compounds previously reported in the literature, show that conjugating the degenerate Cope rearrangements of barbaralane (1a) and several semibullvalenes (3a, 7a, 8a), and for those of a subsituents (e. g. aryl, CN, CO 2 R) in the 2,6 positions lower the barriers of the degenerate Cope rearrangement, whereas number of their 3,7-and 2,6-disubstituted derivatives, have been determined by variable-temperature carbo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
53
1

Year Published

2001
2001
2013
2013

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 28 publications
(58 citation statements)
references
References 0 publications
4
53
1
Order By: Relevance
“…This is confirmed by consideration of the HOMOs and the electron localization function (ELF; see below). Note that for some substituted semibullvalenes it was previously observed that shortening of the 1,5‐bridge is accompanied by opening of the cyclopropane ring,4 as can be seen in tetraphosphabarbaralane in Figure 2. Thus, the symmetrical phosphabarbaralane is achieved by two geometrical changes: 1) the C1‐C9‐C5 bridge is shortened, and 2) the angle at C1 is enlarged, that is, the C2C8 bond is elongated.…”
Section: Barrier Heights δE=e${{{\rm El}\hfill \Atop C_{{\rm 2v}}\hfimentioning
confidence: 61%
See 3 more Smart Citations
“…This is confirmed by consideration of the HOMOs and the electron localization function (ELF; see below). Note that for some substituted semibullvalenes it was previously observed that shortening of the 1,5‐bridge is accompanied by opening of the cyclopropane ring,4 as can be seen in tetraphosphabarbaralane in Figure 2. Thus, the symmetrical phosphabarbaralane is achieved by two geometrical changes: 1) the C1‐C9‐C5 bridge is shortened, and 2) the angle at C1 is enlarged, that is, the C2C8 bond is elongated.…”
Section: Barrier Heights δE=e${{{\rm El}\hfill \Atop C_{{\rm 2v}}\hfimentioning
confidence: 61%
“…Much effort was made to find a symmetrical ground‐state structure by studying various derivatives experimentally and theoretically (e.g., semiempirical MO calculations2, 3). The most valuable overview was given by Quast et al4 Additional reviews can be found in refs. 1, 5, 6 and references cited therein.…”
Section: Barrier Heights δE=e${{{\rm El}\hfill \Atop C_{{\rm 2v}}\hfimentioning
confidence: 99%
See 2 more Smart Citations
“…[3Ϫ9] These values were calculated from coalescence temperatures in variable temperature NMR experiments and therefore, strictly speaking, refer only to a single temperature. Recent advances in NMR technology, especially in currently available devices for controlling temperature stability in variable temperature NMR experiments, [10] have encouraged us to readdress the problem of investigating rotational NϪO barriers over a broader temperature range in order to derive more significant activation parameters (∆H ‡ , ∆S ‡ ) for this dynamic process. In view of the above mentioned issues we selected a small set of newly available heterocyclic N-alkoxides as probes [N-Isopropoxy-2(1H)-pyridinethione (1) and the 4-substituted thiazolethiones 2 and 3, Figure 1 …”
Section: Introductionmentioning
confidence: 99%